Minimising injuries in gymnastics activities - Hume, P. (coachesinfo.com)
Injury is currently a cause of impaired performance for elite New Zealand gymnasts. Maintenance and improvement in gymnastics performance by reducing the risk of injury is desirable. This paper aims to a) outline the incidence and nature of gymnastics injury and the evidence in the literature for risk factors associated with gymnastics injury, and b) to outline a prospective study currently being conducted with elite New Zealand gymnasts to assess the relationship between injury risk during gymnastic competition and training, and physical and medical factors. Detailed gymnastics training and competing information, and injury report forms are collected. Musculoskeletal, psychological, medical and anthropometric screenings are conducted every three months. Preliminary results indicate that training and musculoskeletal variables are possible risk factors for gymnastics injury.